Does Employability Anxiety Trigger Psychological Distress and Academic Major Dissatisfaction? A Study on Tour Guiding Students - Derya Demirdelen Alrawadieh (Journal of Tourismology)
The tourism and hospitality industry has been severely hit by the ongoing Covid-19 pandemic resulting in much uncertainty about the future of careers within the industry. While current employees have been subject to growing research from different perspectives, little is known about tourism students’ (thus potentially future tourism employees) employability anxiety and how this can influence their well-being and attitudes toward their current academic majors. To fill this gap, this study proposes and assesses a conceptual model linking employability anxiety, psychological distress, perceived social support, and academic major satisfaction. Drawing on data collected from tour guiding students in Turkey, the results show that students’ employability anxiety was significantly associated with increased psychological distress and decreased academic major satisfaction. The study findings fail to support the proposed moderating effect of perceived social support indicating that when anxious about their vocational future, tour guiding students’ levels of psychological distress and academic major dissatisfaction are less likely to be mitigated by perceived social support.